MEASURING THE QUALITY OF COLLEGE LIFE ON AN EXAMPLE OF RUSSIAN UNIVERSITY - Alena I. Nefedova (Высшее образование в России, 2016)
In growing competition between universities from all over the world, the evaluation of student's experience in the university becomes very important and crucial for management decisions. The article discusses the results of applying the method of measuring the quality of university life (QCL - quality of college life), developed by American researchers of higher education on the basis of sociological studies of quality of life. This technique provides a comprehensive assessment of student satisfaction with university experience and can be used not only for internal monitoring and management decision-making, but also for inter-institutional comparisons.